Trigonometric Eq 1
Trigonometric Eq 1
Trigonometric Eq 1
2 sec x – 1 = ( 2 1) tan x.
3. sin 3 + cos 2 = 0
4. sin 3x + cos 2x = 1
5. sin 3x + cos 2x = –2
7
6. sin4x + cos4x = . sinx. cosx.
2
4
7. sec - cosec =
3
x
sec 2
10. 1 + 2 cosec x = 2
2
x
11. 8 tan2 1 sec x
2
FIITJEE Ltd., ICES House, Sarvapriya Vihar (Near Hauz Khas Bus Terminal), New Delhi - 16, Ph : 6515949 , 6865182, 6854102, Fax : 6513942
Page 2 of 7 SANKALP_TE-1
x x
sin 0 or ( 2 1) tan
tan
2 2 8
x x
n or n
2 2 8
x 2n, 2n
4
3. sin 3 + cos 2 = 0
cos 2 = –sin(3) = cos 3
2
2 2n 3 , n I
2
Taking (+ve) sign;
we get 2n
2
Taking (-ve) sign;
We get 5 2n
2
2n
5 10
3
from (i) and (ii), the solutions belonging to 0 are;
2
3 7 11 15 3
, , , ,
10 10 10 10 2
4. (3 sin x – 4 sin3x) + (1 – 2 sin2x) = 1
i.e. –4 sin3x – 2 sin2x + 3 sin x = 0
2 4 48
sin x (4 sin2x + 2 sin x – 3) = 0 sin x 0 or sin x
8
1 13
i.e. sin x 0 or sin x
4
1 13
x = n or x = n + (–1)n sin1
4
1 13
sin x is rejected as it is 1
4
Note: If the equation contains one of the expressions (sin x + cos x) or (sin x – cosx)
and the function sin 2x (or the product sin x cos x) then use the fact.
sin 2x = (sin x + cos x)2 – 1 = 1 – (sin x – cosx)2
5. Since, sin 3x –1 and cos 2x –1. We have, sin 3x + cos 2x –2.
Thus the equality holds true if and only if
sin 3x = –1 and cos 2x = –1
3x n ( 1)n and 2x = 2n
2
n
i.e. x ( 1)n and x n , n 1
3 6 2
Solution set is,
n
x / x ( 1)n x / x n
3 6 2
FIITJEE Ltd., ICES House, Sarvapriya Vihar (Near Hauz Khas Bus Terminal), New Delhi - 16, Ph : 6515949 , 6865182, 6854102, Fax : 6513942
Page 3 of 7 SANKALP_TE-1
Note: Here unlike all other problems the solution set consists of the intersection of
two solution sets and not the union of the solution sets.
7
6. sin4x + cos4x = . sinx. cosx.
2
7
(sin2x + cos2x)2 – 2 sin2x cos2x = sin x. cos x
2
1 7
1 (sin2x)2 (sin 2x)
2 4
2
2 sin 2x + 7 sin 2x – 4 = 0
(2 sin x – 1) (sin 2x + 4) = 0
1
sin 2x or sin 2x 4 1
2
2x n ( 1)n
6
n
i.e., x ( 1)n
2 12
7. Given equation is
4
sec - cosec =
3
1 1 4
or,
cos sin 3
sin cos 4
or,
sin .cos 3
or, 3sin - 3cos = 4sin cos
squaring we get, 9sin2 + 9cos2 - 18sin cos = 4sin22
or, 9 – 9sin2 = 4sin22
or, 4sin22 + 9sin2 - 9 = 0
or, 4sin22 + 12sin2 - 3sin2 - 9 = 0
or, (sin 2 + 3) (4 sin2 - 3) = 0
3
either sin2 = –3 or, sin2 = = sin (suppose)
4
no solution 2 = n + (–1)n
= n ( 1)n .
2 2
3
where = sin–1
4
8. (1 - tan) (1 + sin 2) = (1 + tan)
2 tan
(1 tan ) 1 2
(1 tan )
1 tan
(1 - tan) (1 + tan)2 = (1 + tan) (1 + tan2)
1 – tan2 = 1 + tan2 or tan = –1
tan = 0 or tan = –1
= n or n
4
But 0,
2 2 4
9. We have,
(tan + tan2) + tan 3 = 0
FIITJEE Ltd., ICES House, Sarvapriya Vihar (Near Hauz Khas Bus Terminal), New Delhi - 16, Ph : 6515949 , 6865182, 6854102, Fax : 6513942
Page 4 of 7 SANKALP_TE-1
tan tan2
(1 tan . tan 2) tan3 0
1 tan tan 2
tan ( + 2) (1 - tan tan2) + tan 3 = 0
tan 3 (1 - tan tan2 + 1) = 0
either tan 3 = 0 or 2 - tan tan 2 = 0
2 tan .(2 tan )
i.e., 3 n or 0
1 tan2
n 1
or tan
3 2
n 1
or n , where tan =
3 2
10. Here,
x
sec 2
1 + 2 cosec x = 2
2
1 2 [1 tan x / 2]
2
sin 2
x
i.e. 2[2 1sin x] 1 tan2 sin x
2
x x
2 tan 2 2 tan
2 2 1 tan2 x 2
1 tan2 x 2 1 tan2 x
2 2
x
Put tan t,
2
2t 2t
2 2 (1 t 2 ) 2
1 t 1 t
2
4t2 + 4t + 4 + 2t (1 + t2) =0
2t3 + 4t2 + 6t + 4 = 0
i.e., t3 + 2t2 + 3t + 2 = 0
(t + 1) (t2 + t + 2) = 0
t = –1 ( t2 + t + 2 0)
x x
or tan t 1 n , n I
2 2 4
x = 2n - , n I is the required solution.
2
x 1 cos x
11. We know that tan2 2 1 cos x
x
Given 8 tan2 1 sec x
2
1 cos x 1 1 cos x
or, 8 1
1 cos x cos x cos x
or, 8cosx – 8cos x = (1 + cosx)2
2
tan 2 tan
Q.1 f = 0, then the general value of is
1 tan tan 2
n n n
(A) n ; n I (B) ;nI (C) ; n I (D) ;nI
3 4 6
ANS B
x 3
Q.2 Find the general solution of x, cot
4 3 3
(A) (12n – 1) ; n I
2
(B) (12n + 1) ; n I
2
(C) (12n + 1) ; n I
4
(D) (12n + 1); n I
4
ANS C
FIITJEE Ltd., ICES House, Sarvapriya Vihar (Near Hauz Khas Bus Terminal), New Delhi - 16, Ph : 6515949 , 6865182, 6854102, Fax : 6513942